1988
DOI: 10.1111/j.1474-919x.1988.tb00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional, seasonal and annual variations in the structure of Purple Sandpiper Calidris maritime populations in Britain

Abstract: Samples of Purple Sandpipers were captured around the coasts of Britain. Analysis of their bill‐length distributions enabled the sex ratios and percentages of ‘long‐billed’ and ‘short‐billed’ birds at each locality to be estimated. The sex ratio for the ‘long‐billed’ population was estimated to be one female to 2–11 males, and one female to 1 ‐34 males for the ‘short‐billed’ population. During winter, proportionately more ‘long‐billed’ birds occurred in northern and western Scotland, Wales and southern England… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…Migratory routes between breeding and wintering sites of North American Purple Sandpipers were largely unknown until a recent study confirmed a trans‐Atlantic route from the Canadian Arctic in the summer to Scotland and Ireland in the winter (Summers et al., ). Wintering aggregations of Purple Sandpipers may contain birds from multiple breeding locations (Corse & Summers, ; Nicoll, Summers, Underhill, Brockie, & Rae, ). For example, the majority of Svalbard breeders migrate to the Norwegian coast and western Sweden (Hake, Blomqvist, Pierce, Järås, & Johansson, ), but small numbers winter in northeast Scotland (Summers et al., ) where they mix with individuals from Canada (Summers et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Migratory routes between breeding and wintering sites of North American Purple Sandpipers were largely unknown until a recent study confirmed a trans‐Atlantic route from the Canadian Arctic in the summer to Scotland and Ireland in the winter (Summers et al., ). Wintering aggregations of Purple Sandpipers may contain birds from multiple breeding locations (Corse & Summers, ; Nicoll, Summers, Underhill, Brockie, & Rae, ). For example, the majority of Svalbard breeders migrate to the Norwegian coast and western Sweden (Hake, Blomqvist, Pierce, Järås, & Johansson, ), but small numbers winter in northeast Scotland (Summers et al., ) where they mix with individuals from Canada (Summers et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to separate males from females, we used measurements proposed by Scebba (2001Scebba ( , 2009) based on a discriminant analysis of wing length. Frequency distributions of wing length were analysed using Harding-Cassie plots on arithmetic probability paper (Harding 1949, Cassie 1954, Griffiths 1968, Nicoll et al 1988, a graphical method for separating superimposed normal distributions. This analysis was based on the assumption that wing lengths of Skylark populations migrating along the southern Tyrrhenian coastline would be normally distributed.…”
Section: Discussionmentioning
confidence: 99%
“…Circles -sexed on bill length, squares -sexed on gonads, triangles -molecularly sexed. The data were from this study, Belopolski (1941), Nicoll et al (1988), Summers et al (1990b), Hake et al (1997), Mittelhauser et al (2006), Strann & Summers (2006), Summers (2007), Foster et al (2010), Hallgrimsson et al (2011) and Guyonnet et al (2011).…”
Section: Discussionmentioning
confidence: 99%